2018
DOI: 10.1002/ange.201800672
|View full text |Cite
|
Sign up to set email alerts
|

An Iron Complex with a Bent, O‐Coordinated CO2 Ligand Discovered by Femtosecond Mid‐Infrared Spectroscopy

Abstract: The activation of carbon dioxide by transition metals is widely recognized as akey step for utilizing this greenhouse gas as arenewable feedstockfor the sustainable production of fine chemicals.H owever,t he dynamics of CO 2 binding and unbinding to and from the ligand sphere of ametal have never been observed in the time domain. The ferrioxalate anion is used in aqueous solution as au nique model system for these dynamics and femtosecond UV-pump mid-infrared-probe spectroscopyi sa pplied to explore its photoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The d-LMCT state showed dissociative character under both of these constraints, but the rate at which bond elongation lowered the energy during the initial bond stretching was much greater when stretching C1–C2 than when stretching Fe–O1, suggesting that a molecule placed on the d-LMCT surface at the b-LMCT minimum would see its C1–C2 bond elongate first. This picture is consistent with recent experiments showing that a CO 2 molecule is released first, leaving behind [Fe­(ox) 2 (CO 2 )] 3– . However, the photochemical process initiated by excitation to b-LMCT does not start in the dissociative d-LMCT state, so we must now turn to a more careful analysis of how easy it is for the state character to switch.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The d-LMCT state showed dissociative character under both of these constraints, but the rate at which bond elongation lowered the energy during the initial bond stretching was much greater when stretching C1–C2 than when stretching Fe–O1, suggesting that a molecule placed on the d-LMCT surface at the b-LMCT minimum would see its C1–C2 bond elongate first. This picture is consistent with recent experiments showing that a CO 2 molecule is released first, leaving behind [Fe­(ox) 2 (CO 2 )] 3– . However, the photochemical process initiated by excitation to b-LMCT does not start in the dissociative d-LMCT state, so we must now turn to a more careful analysis of how easy it is for the state character to switch.…”
supporting
confidence: 92%
“…Regarding theoretical studies, density functional theory (DFT) and time-dependent DFT (TD-DFT) have been used to investigate the LMCT state of PFS. 11,12,21,22 While DFT is only able to optimize the lowest state of a given spin multiplicity, TD-DFT faces well-known challenges when modeling chargetransfer excitations. 23,24 The complete active space selfconsistent field (CASSCF) method with state-averaging optimization has been widely used for excited states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vöhringer et al . have depicted the C=O stretching frequency at 1681 cm −1 for ferrous dioxalate CO 2 complex [24] . Murray et al .…”
Section: Resultsmentioning
confidence: 99%
“…Vöhringer et al have depicted the C=O stretching frequency at 1681 cm À 1 for ferrous dioxalate CO 2 complex. [24] Murray et al have shown the asymmetric CO 2 stretching of the reaction mixture at 1676 cm À 1 and 1657 cm À 1 for two different Fe-complexes. [25] The ESI mass spectra recorded after the bulk electrolysis of Fc-NAP 2 shows the presence of CO 2 adduct found (A) CO production at À 1.2 V (balck), À 1.3 V (red), À 1.4 V (blue), À 1.5 V (pink) and, À 1.6 V (green) vs. SCE after 3 h electrolysis.…”
Section: Electrolysis and Product Analysismentioning
confidence: 98%